Discovery of inhibitors against SARS-CoV-2 main protease using fragment-based drug design. (1st February 2023) - Shao, Hai Ping; Wang, Tian Hua; Zhai, Hong Lin; Bi, Ke Xin; Zhao, Bing Qiang
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the etiological agent of coronavirus disease 2019 (COVID-19), in which the main protease (Mpro) plays an important role in the virus's life cycle. In this work, two representative peptide inhibitors (11a and PF-07321332) were selected, and their interaction mechanisms of non-covalently bound with Mpro were firstly investigated by means of molecular dynamical simulation. Then, using the fragment-based drug design method, some fragments from the existing SARS-CoV and SARS-CoV-2 inhibitors were selected to replace the original P2 and P3 fragments, resulting in some new molecules. Among them, two molecules (O-74 and N-98) were confirmed by molecular docking and molecular dynamics simulation, and ADMET properties prediction was employed for further verification. The results shown that they presented excellent activity and physicochemical properties, and had the potential to be new inhibitors for SARS-CoV-2 main protease. Highlights: Interaction characteristics of SARS-CoV-2 Mpro with peptide inhibitor inhibitors. Two peptide inhibitors against SARS-CoV-2 Mpro have potential for optimization. Efficient optimization of peptide inhibitors P2 and P3 fragments using a fragment-based drug discovery approach. Two molecules found to have potent inhibitory activity against SARS-CoV-2 Mpro.